Vliyanie tabakokureniya na zdorov'e i massu telacheloveka (Ожирение и метаболизм, 2010)
Tobacco smoking causes a lot of human deseases and is one of the main reasons of premature death. Smoking cessation is very important for the patient's health but difficult for them due to development of nicotine dependence. Tobacco dependence is a chronic disease. Smoking Cessation Clinical Practice Guideline, published in 2008, emphasize the dire health consequences of tobacco dependence, regulate the way of treating patients who want to quit smoking, recommending the use of effective treatments, including counseling and medications. Seven first-line medications (5 nicotine and 2 non-nicotine, including Varenicline) that reliably increase long-term smoking abstinence rates are now available. Smoking cessation is accompanied by a moderate weigh gain. And its a strong motivational factor to continue smoking, espcially for women. Сounseling, healthy food and physical activity are recommended for such patients.